The Impact of Digital Transformation on Contextual Performance: A Field Study at the Universities of Fezzan and Sirte - Hasan Emran; Fouzi Albdri (APPS Publications, 2025)
This study aims to examine the impact of digital transformation on contextual performance at the Universities of Sirte and Fezzan. The study population consists of faculty members working at both universities, and data were collected using a structured questionnaire. The study sample included 148 participants. To achieve the research objectives and test the hypotheses, a descriptive correlational approach was employed.The analysis produced several findings, the most significant of which indicates a statistically significant impact of digital transformation on contextual performance at the universities under study. Accordingly, the study recommends giving greater attention to performance management—particularly contextual performance—due to its substantial role in achieving high levels of institutional success.